Effect of Surgeon Volume and Craniofacial Fellowship Training on Cleft Palate Complication Rates. (May 2017) - Schoenbrunner, Anna R.; Dalle Ore, Cecilia L.; Lance, Samuel; McIntyre, Joyce; Jones, Marilyn; Gosman, Amanda
Abstract : Background: Both the general and pediatric surgical literature have evidenced an inverse relationship between surgical case volume and complications. This study seeks to ascertain the relationship between case volume and fistula rates in cleft palate patients. We also seek to determine if craniofacial fellowship training impacts fistula rates. Methods: Charts were reviewed at a multidisciplinary cleft center in San Diego, CA. We performed chart review on 207 nonsyndromic patients with cleft lip and palate who had surgery at our institution from 1988 to 2010. Data were analyzed using independent samples t test, χ 2 test, and stepwise binary logistic regression to assess whether surgeon case volume and craniofacial fellowship training correlated with fistula repair rate. Results: The surgeon with the highest volume had significantly fewer fistula repairs than lower volume surgeons ( P = 0.044). Patients operated on by the craniofacial fellowship trained surgeon had significantly fewer fistulas compared with other plastic surgeons who performed cleft palate surgery ( P = 0.005). Conclusions: Based on our retrospective review, it does appear that both high case volume and craniofacial fellowship training are associated with fewer postoperative fistulas.